(untitled) (Research Journal of Mathematics & Technology, 2022)
In the first paper of this series, we discussed selected geometric concepts related to the class of patterns referred to as gereh. The creation of these patterns followed the rules of gereh (axioms). Constructions of such patterns follow three steps: construction of the contour for the pattern template, construction of tessellation inside the contour, and designing a pattern for each tessellation tile. In this part, we will discuss why some patterns are considered incorrect and what are the fundamental features of a geometric pattern that make it acceptable?